Meta Analisis: Potensi Faktor Usia dan Jenis Kelamin pada Kejadian Depresi di Masa Pandemi Covid-19 - Suminanto Suminanto; Aris Widiyanto; Aquartuti Tri Darmayanti; Dewi Arradini; Rina Tri Handayani; Joko Tri Atmojo (Persatuan Perawat Nasional Indonesia (PPNI) Jawa Tengah, 2021)
The consistent negative psychosocial impact of the COVID-19 pandemic is mental health disorders in the form of depression. Various studies have shown that several factors can influence, such as gender and age. The purpose of this meta-analysis is to measure the influence of gender and age on the incidence of depression during the COVID-19 pandemic in various countries. Database searches were conducted from January-March 2021. Databases included PubMed, Google Scholar, NIH, CDC, and Science Direct. Key words include: “COVID 19 and depression” and “COVID 19 and depression and adjusted Odds Ratio”, “COVID 19 and depression and age” and “COVID 19 and depression and age and adjusted odds ratio”. 5 articles included to quantitative analysis. People aged ≥ 25 years were 2.65 times more likely to experience depression although the result was not significant OR 2.65 (95% CI 0.98-7.18; P = 0.05). Women had 1.77 times the risk of experiencing depression than men and it was statistically significant OR 1.77 (95% CI 1.36-.2.28; P <0.001).